2004
DOI: 10.1124/jpet.104.066902
|View full text |Cite
|
Sign up to set email alerts
|

Mentholated Cigarette Smoking Inhibits Nicotine Metabolism

Abstract: Smoking mentholated cigarettes has been suggested to convey a greater cancer risk compared with smoking nonmentholated cigarettes. Two of the possible mechanisms by which mentholated cigarette smoking could increase risk are by increasing systemic exposure to tobacco smoke toxins and by affecting the metabolism of nicotine or tobacco smoke carcinogens. To examine these possibilities, we performed a crossover study in 14 healthy smokers, one-half of whom were African-Americans and one-half whites. Subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
161
4
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(187 citation statements)
references
References 30 publications
14
161
4
5
Order By: Relevance
“…The present biomarkers findings are consistent with the weight of extant epidemiologic evidence (22,24) and prior biomarkers studies (36,40) suggesting that exposures and consequent risks attending the smoking of mentholated cigarettes are not substantially different from those of nonmentholated cigarettes. …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The present biomarkers findings are consistent with the weight of extant epidemiologic evidence (22,24) and prior biomarkers studies (36,40) suggesting that exposures and consequent risks attending the smoking of mentholated cigarettes are not substantially different from those of nonmentholated cigarettes. …”
Section: Discussionsupporting
confidence: 78%
“…The estimate of 0.625 mg menthol delivery to the smoker per cigarette smoked that was developed by Benowitz and colleagues (36) is in fair agreement with an estimated systemic delivery that might be developed from the 0.34 mg menthol per cigarette smoke yield reported here from standardized machine smoking. The recent development of improved methods to measure the lung deposition and retention of individual cigarette smoke constituents in human smokers (41,42) suggests that better estimates of both local and systemic exposures to menthol or to other smoke constituents of greater toxicologic interest may soon be attainable.…”
Section: Discussionsupporting
confidence: 74%
“…Although there have been reports of higher cotinine levels among menthol smokers [14,16], most studies are not in accord with these findings [18][19][20][21][22][23], and we observed adjusted cotinine levels non-significantly lower in this group. White female menthol smokers in fact had the highest intensity of smoking but the lowest average cotinine levels (Fig.…”
Section: Discussioncontrasting
confidence: 55%
“…1). It has been hypothesized that menthol cigarettes may intensify smokingrelated lung cancer risk through a variety of physiological mechanisms or by altering smoking behavior (e.g., by facilitating deeper inhalation) [5,21]. A recent investigation measuring smoking topography, however, reported slightly lower puff volume among menthol compared with non-menthol smokers [24].…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that smoking cigarettes containing menthol interferes with nicotine glucuronidation 49) the catalysts of which are assumed to be UGT2B10 and UGT1A4. 50,51) Monoterpenoid alcohols interfere with propofol glucuronidation catalyzed by UGT1A9.…”
Section: Discussionmentioning
confidence: 99%